The consumers' understandings towards halal food products in Malaysia - Ismail, Kamarulzaman; Nordin, Mohammad Fahmi; Awang, Mohd Daud; Baharum, Nur Bahirah (Penerbit UNIPSAS, 2022)
Research on the effect of consumers’ understandings towards halal food are not well versed in terms of getting good finding and recommendation to halal industry. Although the data of halal consumers throughout the world are rapidly increasing especially among Muslims, related studies to indicate the influence of using halal products among consumers are still in its infancy level. Hence, a conceptual study needs to be conducted to explore and acknowledge several elements that might affect consumers’ action towards halal products and product purchase. The theoretical framework consists of the elements of perception, knowledge, religion, and halal certification are considered important in influencing consumers and their behaviours in the purchase.